Sosialisasi dan Edukasi Perilaku Anti Korupsi Bagi Siswa Kelas 5 di Madrasah Ibtidaiyah Darussyifa Al-Musri’ 1 - Adryan Putra Pratama; Alya Fitri; Diela Jauza (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The problem of corruption in Indonesia is increasingly widespread. The impact of corruption can damage democratic values, morallity and social rights so that there needs to be preventive action in the form of planting anti- corruption values for all levels of society, especially in early childhood. Therefore, an anti-corruption behavior socialization was held for students at MI Darussyifa Al-Musri 1 which aims to give them an understanding of the basic principles of anti-corruption and how to apply them in everyday life so that they can build an anti-corruption personality as the nation's successor. The methods used in this activity were material exposure through presentations and video shows, discussions, and questions and answers. The results of this study show that students are able to identify anti-corruption behaviors based on the material and videos that have been shown previously so that it can be said that this activity meets the indicators of program success. Through this socialization activity, students are increasingly aware that corruption is not only a legal case that causes the state to lose money but all forms of fraudulent acts and by applying anti-corruption values it is hoped that it will suppress the habit of corruptive behavior in any form. The implication of the results of this study is that students know the acts of corruption that occur in everyday life and are encouraged not to do so in the future.